2003
DOI: 10.1016/s0002-9440(10)63681-4
|View full text |Cite
|
Sign up to set email alerts
|

Integrin αvβ8-Mediated Activation of Transforming Growth Factor-β Inhibits Human Airway Epithelial Proliferation in Intact Bronchial Tissue

Abstract: Transforming growth factor (TGF)-beta is a potent multifunctional cytokine that is an essential regulator of epithelial proliferation. Because TGF-beta is expressed almost entirely in a latent state in vivo, a major source of regulation of TGF-beta function is its activation. A subset of integrins, alphavbeta8 and alphavbeta6, which are expressed in the human airway, has recently been shown to activate latent TGF-beta in vitro, suggesting a regulatory role for integrins in TGF-beta function in vivo. Here we ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 34 publications
1
51
0
Order By: Relevance
“…Thus, we found that the integrin ␣ v ␤ 8 is expressed at high levels in fragments of intact bronchial tissues and that it mediates activation of TGF-␤, ultimately inhibiting epithelial cell growth. 20 These findings suggest a possible role for TGF-␤ during the reactivation of the EMTU in the injured adult airway. However, the EMTU has only been rigorously experimentally defined in nonhuman lung systems, which have significant differences in anatomy and cell-type distribution from human lungs.…”
mentioning
confidence: 84%
“…Thus, we found that the integrin ␣ v ␤ 8 is expressed at high levels in fragments of intact bronchial tissues and that it mediates activation of TGF-␤, ultimately inhibiting epithelial cell growth. 20 These findings suggest a possible role for TGF-␤ during the reactivation of the EMTU in the injured adult airway. However, the EMTU has only been rigorously experimentally defined in nonhuman lung systems, which have significant differences in anatomy and cell-type distribution from human lungs.…”
mentioning
confidence: 84%
“…The 3 0 -untranslated region (3 0 UTR) of integrinb8 harbors a typical target sequence for miR-93 ( Figure 6a). It has been reported that integrin-b8 can function as a negative regulator of cell proliferation when activated by tumor growth factor-b (Cambier et al, 2000;Fjellbirkeland et al, 2003). We analyzed integrin-b8 expression in tumor sections and cells expressing miR-93.…”
Section: Mir-93 Represses Integrin-b8 Expressionmentioning
confidence: 99%
“…Our results suggest that expression of integrin-b8 can facilitate cell death. It has been reported that integrin-b8 is a negative regulator of cell proliferation (Fjellbirkeland et al, 2003;Cambier et al, 2005). The reduced levels of integrin-b8 on the tumor cell surface may favor endothelial cell activities and angiogenesis.…”
Section: Integrin-b8 Mediates Mir-93 Functionsmentioning
confidence: 99%
“…(d) Airway fibroblasts respond to IL-1β by increasing β8 expression and αvβ8-mediated TGF-β activation. Increased TGF-β activation by airway fibroblasts causes (e) autocrine effects on the fibrogenic fibroblast phenotype by increasing Col I and αSMA and (f) paracrine effects on adjacent airway epithelium, which inhibits epithelial proliferation (10,44,66) and contributes to the increased expression of β6 by adjacent airway epithelial cells, forming a self-amplifying loop of TGF-β activation.…”
Section: Figure 10mentioning
confidence: 99%